Penerapan Data Mining Dalam Prediksi Penjualan Prabot Rumah Tangga Menggunakan Metode Apriori Pada Toko Hasanah Mart - Silalahi, Natalia (Building of Informatics, Technology and Science (BITS), 2020)
The application of data mining is very well done, especially in predicting transaction patterns that are very often done in the sale and purchase of household furniture, household furniture is goods that are very much in demand by many groups, especially mothers, the higher the amount of demand, the more data transactions that must be processed, dug up to obtain the desired information and needed a method approach to processing transaction patterns that are the most desirable so that a store or company can sort out the inventory of goods that must be met based on the level of market needs, appropriate methods and has been widely used in one of the sales prediction is the Apriori method is a method that uses association rules that aim to see the associative relationship between a combination of items with other items, in data mining using the a priori method can also be done with very much data from and processed with a fast time and a very good level of data prediction accuracy.